The Samurai of Sales : The Path to True Sales Mastery. - Harris, Mitch (Morgan James Publishing, 2018)
The goal of The Samurai of Sales is to give the reader an arsenal of real life selling skills that he can use to generate massive sales and consistently outperform the competition, while cultivating the realization that when done properly, being in professional sales is one of the most amazing privileges on the planet.
Description based upon print version of record.
Keywords: Selling.; Vente.; selling.; Selling